Combination treatment of vildagliptin and bay leaf (Syzygium polyanthum) extract increased pancreatic beta cells number but have no effect toward glycated albumin levels in diabetic male Wistar rats (Rattus norvegicus) - Meiyati Panambunan; Wimpie Pangkahila; Anak Agung Gede Budhiarta (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2019)
Introduction: Diabetes mellitus is a complex and progressive disease which often lead to several debilitating complications that partly caused by by free radicals which can be overcome with antioxidants. Bay leaves contain essential oils, tannins, flavonoids and terpenoids which have considerable antioxidant properties. Therefore, this study aims to determine the effect combination treatment of vildagliptin and bay leaf (Syzygium polyanthum) extract toward pancreatic beta cells density and glycated albumin levels in diabetic male Wistar rats (Rattus norvegicus). Methods: An experimental posttest only control group study was conducted using 36 albino male rats, aged 2-3 months, weighing 180-200 grams. The rats were divided into 2 groups (n= 18) with control group treated with 1.8mg/200g body weight vildagliptin and 2cc placebo (aquabidest) while the treatment group received 1.8mg/200g BW vildagliptin and 250 mg/200g BW bay leaves extract. All treatment lasted for 21 days. Results: The results showed that pancreatic beta cell counts in the treatment group was significantly higher than the control group (109.07 ± 20.47 cells/field of view vs 90.87 ± 13.91 cells/field of view; p<0.01). However, the levels of Glycated albumin between two groups were not significantly different (treatment vs control: 17.33 ± 4.51 vs 20.18 ± 4.57; p=0.068). Conclusion: This study suggested that combination treatment of vildagliptin and bay leaf extract increased pancreatic beta cells but did not reduce glycated albumin levels in diabetic male Wistar rats.